Metode Behavior Kontrak Dalam Meningkatkan Kedisiplinan Membereskan Mainan di Dalam Kelas Pada Anak Usia 4-5 Tahun - Maslinawati Maslinawati; Elnawati Elnawati; Redi Awal Maulana (PT. Alahyan Publisher Sukabumi, 2025)
Early childhood discipline, especially in cleaning up toys in the classroom, is an important aspect that needs to be developed from an early age. This study aims to determine the effectiveness of the application of the contract behavior method in improving the discipline of 4-5 year old children in Kober [name Kober]. The research method used is Classroom Action Research (PTK) which consists of two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews, and documentation, then analyzed in a qualitative and quantitative descriptive manner. The subjects of the study were 15 children aged 4-5 years who showed a low level of discipline in cleaning up toys. The contract behavior method is applied by providing mutual agreement between teachers and children regarding positive consequences (reward) and negative consequences (punishment) according to the behavior shown. The results of the study show that the application of the contract behavior method can significantly improve children's discipline. In pre-action, only 40% of children are disciplined in cleaning up toys. After the first cycle, the percentage increases to 70%, and by the end of the second cycle it reaches 90%. Children become more aware of the importance of discipline and feel motivated to clean up toys with attractive rewards and appropriate punishments. This study concludes that the contract behavior method is effective in improving early childhood discipline in cleaning up toys. It is recommended that teachers and parents can apply this method consistently to build positive discipline habits in children from an early age.